Application of tranexamic acid and diluted epinephrine in primary total hip arthroplasty. Issue 5 (July 2018) - Wu, Yuangang; Zeng, Yi; Bao, Xianchao; Xiong, Huazhang; Fan, Xiwei; Shen, Bin
Abstract : N/A: Tranexamic acid (TXA) and diluted epinephrine (DEP) has been reported to be an efficient and well tolerated way for reducing blood loss in total hip arthroplasty (THA). This meta-analysis was designed to compare the effectiveness of combination application of TXA with DEP in primary THA. The following electronic databases were searched, including PubMed, EMBASE, Web of Science, the Cochrane Library, China National Knowledge Infrastructure and Google Search Engine, for published studies involving the TXA with DEP in primary THA. All randomized controlled trials (RCTs) were included. Statistical analysis was assessed using RevMan 5.3 software. Five independent RCTs were included, with a total sample size of 496 patients. The application of TXA with DEP can significantly reduce total blood loss (mean difference, 246.13; 95% CI, −369.95 to −122.32; P < 0.0001), hidden blood loss (mean difference, 299.98; 95% CI −433.61 to −166.35; P < 0.0001) and transfusion requirements (risk ratio, 0.50; 95% CI 0.28–0.90; P = 0.02) compared with the TXA alone. There were no significant differences in intraoperative blood loss ( P = 0.46), drainage volume ( P = 0.61), length of stay ( P = 0.53) and the rate of DVT ( P = 0.56) between the two groups. On the basis of current evidence, this meta-analysis showed that the application TXA with DEP is a well tolerated and efficacious treatment to reduce total blood loss, hidden blood loss and transfusion requirements in primary THA, without increasing the risk of DVT in primary THA.